2007
DOI: 10.1080/13549830701656960
|View full text |Cite
|
Sign up to set email alerts
|

Governing Climate Adaptation in the Local Arena: Challenges of Risk Management and Planning in Sweden

Abstract: This paper directs attention to conditions for climate adaptation as an important part of governing climate change in the local arena. Empirical focus is put on attempts to manage flood risks by means of risk management and planning in two Swedish municipalities. Following the need to widen our understanding of how, when and under what conditions climate adaptation occurs, three challenges are particularly emphasized from the case studies: facing the safety vs. scenery conflict where political priorities and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(100 citation statements)
references
References 18 publications
(26 reference statements)
4
90
0
6
Order By: Relevance
“…Amundsen, Berglund, & Westskog, 2010;Carter, 2011;Nalau, Preston, & Maloney, 2015;Storbjörk, 2007;Termeer, Dewulf, & Breeman, 2013;Wamsler & Brink, 2014), which results in a stalemate and a lack of climate adaptation action (Fünfgeld, 2010;Urwin & Jordan, 2008;Williams et al, 2013). If vague responsibilities hamper climate adaptation, conversely a more explicit allocation of responsibilities could drive climate adaptation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Amundsen, Berglund, & Westskog, 2010;Carter, 2011;Nalau, Preston, & Maloney, 2015;Storbjörk, 2007;Termeer, Dewulf, & Breeman, 2013;Wamsler & Brink, 2014), which results in a stalemate and a lack of climate adaptation action (Fünfgeld, 2010;Urwin & Jordan, 2008;Williams et al, 2013). If vague responsibilities hamper climate adaptation, conversely a more explicit allocation of responsibilities could drive climate adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…The number of empirical studies on the governance of adaptation and the division of responsibilities is gradually increasing, but those studies are conducted on a case-by-case basis (e.g. Amundsen et al, 2010;Fünfgeld, 2010;Lundqvist & Von Borgstede, 2008;Storbjörk, 2007;Wamsler & Brink, 2014). A systematic empirical analysis of governance arrangements for climate adaptation and their underlying rationales is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In a UK context it was found that urban development in flood-prone areas continues to be allowed (Burningham et al 2008). In various other European countries, it was shown that parties interested in the continuation of urban development implicitly tend to believe that Bwater managers should enable spatial planning wherever spatial planners want them to do this Immink 2006: Woltjer andAl 2007;Pardoe et al 2011). Baubion (2015) for instance points at the presence of financial mechanisms that automatically compensate for flood losses and therefore trigger ongoing building activities in flood prone areas in Paris.…”
Section: Implementing Flood Risk Preventionmentioning
confidence: 99%
“…A first barrier is that water managers and spatial planners generally operate through different modes of governance: water management in Europe tends to be centralised, while local governments have the dominant role in spatial planning (Wilson 2006;Storbjörk 2007).…”
Section: Implementing Flood Risk Preventionmentioning
confidence: 99%
“…Studies at the national level are generally characterised by a thematic approach, such as spatial planning (Wilson 2006), agriculture and national resources (Pearson et al 2011;Meinke et al 2009;Steffen et al 2011), flood risk management (Rosenzweig and Wilbanks 2010;Rosenzweig and Solecki 2010) or the governance of climate research (Pielke 2009;Sarewitz and Pielke 2007;Pielke 2010b;Termeer et al 2011;Storbjörk 2007).…”
Section: Introductionmentioning
confidence: 99%